Geomorphic effectiveness, sandur development, and the pattern of landscape response during jökulhlaups: Skeiöarársandur, southeastern Iceland - Magilligan, F. J.; Gomez, B.; Mertes, L. A. K.; Smith, L. C.; Smith, Norman D.; Finnegan, D.; Garvin, J. B. (DigitalCommons@University of Nebraska - Lincoln, 2002)
By contrast with other historical outburst floods on Skeióarársandur, the 1996 jökulhlaup was unprecedented in its magnitude and duration, attaining a peak discharge of ~53,000 m3/s in <17 h. Using a combination of field sampling and remote sensing techniques (Landsat TM, SAR interferometry, airphotos, and laser altimetry), we document the sandur-wide geomorphic impacts of this event. These impacts varied widely across the Skeióarársandur and cannot be singularly attributed to jökulhlaup magnitude because pre-jökulhlaup glacial dynamics and the extant setting largely conditioned the spatial pattern, type, and magnitude of these impacts. Topographic lowering and asymmetric retreat of the ice front during the late twentieth century has decoupled the ice sheet from the moraine/sandur complex along the central and western sandur. This glacial control, in combination with the convex topography of the proximal sandur, promoted a shift from a primarily diffuse-source braided outwash system to a more point-sourced, channelized discharge of water and sediment. Deposition dominated within the proglacial depression, with approximately 3.8*107 m3 of sediment, and along channel systems that remained connected to subglacial sediment supplies. This shift to a laterally dissimilar, channelized routing system creates a more varied depositional pattern that is not explicitly controlled by the concave longitudinal profile down-sandur. Laterally contiguous units, therefore, may vary greatly in age and sediment character, suggesting that current facies models inadequately characterize sediment transfers when the ice front is decoupled from its sandur. Water was routed onto the sandur in a highly organized fashion; and this jökulhlaup generated major geomorphic changes, including sandur incision in normally aggradational distal settings and eradication of proximal glacial landforms dating to ~A.D. 1892.